Multimodal nutritional rehabilitation improves clinical outcomes of malnourished patients with chronic respiratory failure: a randomised controlled trial. Issue 11 (23rd June 2011) - Pison, Christophe M; Cano, Noël J; Chérion, Cécile; Caron, Fabrice; Court-Fortune, Isabelle; Antonini, Marie-Thérèse; Gonzalez-Bermejo, Jésus; Meziane, Lahouari; Molano, Luis Carlos; Janssens, Jean-Paul; Costes, Frédéric; Wuyam, Bernard; et al.
Abstract : Background: In chronic respiratory failure (CRF), body composition strongly predicts survival. Methods: A prospective randomised controlled trial was undertaken in malnourished patients with CRF to evaluate the effects of 3 months of home rehabilitation on body functioning and composition. 122 patients with CRF on long-term oxygen therapy and/or non-invasive ventilation (mean (SD) age 66 (10) years, 91 men) were included from eight respiratory units; 62 were assigned to home health education (controls) and 60 to multimodal nutritional rehabilitation combining health education, oral nutritional supplements, exercise and oral testosterone for 90 days. The primary endpoint was exercise tolerance assessed by the 6-min walking test (6MWT). Secondary endpoints were body composition, quality of life after 3 months and 15-month survival. Results: Mean (SD) baseline arterial oxygen tension was 7.7 (1.2) kPa, forced expiratory volume in 1 s 31 (13)% predicted, body mass index (BMI) 21.5 (3.9) kg/m 2 and fat-free mass index (FFMI) 15.5 (2.4) kg/m 2 . The intervention had no significant effect on 6MWT. Improvements (treatment effect) were seen in BMI (+0.56 kg/m 2, 95% CI 0.18 to 0.95, p=0.004), FFMI (+0.60 kg/m 2, 95% CI 0.15 to 1.05, p=0.01), haemoglobin (+9.1 g/l, 95% CI 2.5 to 15.7, p=0.008), peak workload (+7.2 W, 95% CI 3.7 to 10.6, p<0.001), quadriceps isometric force (+28.3 N, 95% CI 7.2 to 49.3, p=0.009), endurance time (+5.9 min, 95% CI 3.1 to 8.8, p<0.001) and, in women, Chronic Respiratory Questionnaire (+16.5 units, 95% CI 5.3 to 27.7, p=0.006). In a multivariate Cox analysis, only rehabilitation in a per-protocol analysis predicted survival (HR 0.27, 95% CI 0.07 to 0.95, p=0.042). Conclusions: Multimodal nutritional rehabilitation aimed at improving body composition increased exercise tolerance, quality of life in women and survival in compliant patients, supporting its incorporation in the treatment of malnourished patients with CRF. Clinical Trial number: NCT00230984.